Effectiveness of SMS Advertising (A Study of Young Customers in Bahrain) (Global Journal of Management and Business Research, 2014)
Mobile advertising gives companies an opportunity to directly communicate with their consumers beyond the boundaries of time and space. Although mobile advertising is emerging as a promising advertising channel, its effectiveness is still uncertain and requires more investigation. This paper recruited 247 young mobile users in Bahrain and analyzed their reactions to and perceptions of SMS advertising. The study found that these young consumers' attitudes towards SMS advertising were determined by five SMS attributes: entertainment value, informativeness, credibility, personali-zation, and irritation level. The study also found that attitude plays a significant role in determining consumers' future buying behavior, in terms of their intention to use SMS advertising as well as their word-of-mouth (WOM) response to it.
Keywords: mobile marketing; SMS advertising; mobile advertising channel; advertising effectiveness; SMS credibility; SMS informativeness; SMS irritation; SMS pe